1994
DOI: 10.1128/iai.62.9.3753-3760.1994
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 3-hydroxy iC17:0 in subgingival plaque and gingival tissue samples: relationship to adult periodontitis

Abstract: Gram-negative organisms incorporate hydroxy fatty acids into the lipid A moiety of lipopolysaccharide (LPS), and in the case of some members of the family Enterobacteriaceae, hydroxy fatty acids are incorporated exclusively into lipid A. However, a limited number of Bacteroides species have been shown to incorporate several classes of 3-hydroxy fatty acids, particularly 3-hydroxy iC17:0, into constitutive lipids as well as LPS. The present study examined the distribution of hydroxy fatty acids in two periodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 21 publications
(21 reference statements)
0
27
0
Order By: Relevance
“…12 This is probably due to the unique chemical features of the lipid A moieties of these LPSs, such as the presence of 15-methylhexadecanoate in P. gingivalis, 10,13±15 and 3-hydroxy-15-methylhexadecanoate in P. intermedia. 16 Because Gram-negative bacteria belonging to the family Rhizobiaceae infect plants instead of animals, and because the structure of their lipid A exhibits several major differences when compared with lipid A of enterobacteria, we decided to examine the in¯uence of some LPSs isolated from this family of bacteria on cells from normal and LPS-hyporesponsive mice. Bone marrow cells (BMC) represent interesting cellular targets because we established in several previous studies that an LPS receptor of low af®nity, distinct from CD14, is constitutively present on these cells, 17 and that the interaction of Salmonella LPS with this receptor triggers the expression of CD14.…”
Section: Introductionmentioning
confidence: 99%
“…12 This is probably due to the unique chemical features of the lipid A moieties of these LPSs, such as the presence of 15-methylhexadecanoate in P. gingivalis, 10,13±15 and 3-hydroxy-15-methylhexadecanoate in P. intermedia. 16 Because Gram-negative bacteria belonging to the family Rhizobiaceae infect plants instead of animals, and because the structure of their lipid A exhibits several major differences when compared with lipid A of enterobacteria, we decided to examine the in¯uence of some LPSs isolated from this family of bacteria on cells from normal and LPS-hyporesponsive mice. Bone marrow cells (BMC) represent interesting cellular targets because we established in several previous studies that an LPS receptor of low af®nity, distinct from CD14, is constitutively present on these cells, 17 and that the interaction of Salmonella LPS with this receptor triggers the expression of CD14.…”
Section: Introductionmentioning
confidence: 99%
“…Flavobacterium and Myxobacteria are not reported to be constituent organisms of subgingival plaque and the recovery of 3-OH isoC 17:0 in organic solvent and aqueous solvent extracts of plaque and gingival tissue samples is presumed to re¯ect the recovery of Porphyromonas, Prevotella, Bacteroides and Capnocytophaga species only. Using aqueous and organic solvent partitioning, the present study demonstrated that the majority of 3-OH isoC 17:0 (62% of the total) in subgingival plaque samples is recovered in the aqueous phase, most likely in lipopolysaccharide (2). However, 3-OH isoC 17:0 was recovered predominantly in lipid extracts from periodontally hopeless teeth (58% of the total 3-OH isoC 17:0 ) and root samples with visible calculus (67% of the total 3-OH isoC 17:0 ).…”
Section: Discussionmentioning
confidence: 64%
“…This evidence con®rms that the process of sectioning tooth roots contaminated with calculus does not signi®cantly aect the distribution of bacterial lipids. According to a previous report, 58% of the total 3-OH isoC 17:0 in P. gingivalis is recovered in organic solvent extract (2). Of the remaining intraoral organisms tested (Prevotella intermedia, Capnocytophaga ochracea, Capnocytophaga gingivalis and Capnocytophaga sputigena, generously provided by Dr Paulette Tempro, Department of Periodontology, SUNY, Bualo, USA), 3-OH isoC 17:0 is generally incorporated into lipids to an equal or lesser extent than P. gingivalis (data not shown).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations